PRAKTIK HIGIENE DAGING DALAM PENYEMBELIHAN HEWAN QURBAN DI KOTA KUPANG - Aji Winarso; Dodi Darmakusuma; Maxs Urias E Sanam (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2018)
The procedure for handling sacrificed animals has been regulated in Regulation of the Minister of Agriculture - Republic of Indonesia No. 114/Permentan/PD.410/9/2014. This research aims to describe the procedure of slaughter of qurban animals in Kupang City in relation to the provision of safe, health, intact, and halal meat (ASUH). This study is a descriptive study conducted through observation and interviews with qurban committee 1438H (2017M) at two mosques in Kupang City. Assessment is done on how to produce ASUH meat. There are fifteen aspects that are qualitatively assessed, 1 point if fulfilled and 0 if not fulfilled. Total of fulfillment points was then made in a percentage. The hygiene and sanitation practice of qurban slaughter at Al Mujahidin Mosque-Penfui and Darul Hijrah Mosque-Kolhua of Kupang City is quite good with a value of 10/15 (66.67%). Some things that need to be improved are the limitation of personnel with trained people. Meat processing facilities that need to be added is table and basket for meat storage.